Tafsir Ayat-ayat Neurosains (Nasiyah dalam QS. Al-Alaq Ayat 15-16) - Arista, Virandra Adhe; Fadhilah Rahmah MS, Dhinda; Surahman, Surahman; Harmita, Harmita; 'Azizah, Naila Nur; Aziza, Miftah (Lembaga Yasin AlSys, 2022)
In this article, we explain several things related to the concept of nasiyah in QS. Al-Alaq verses 15-16. This study uses a qualitative research approach to the type of literature (library research). Sources of data taken in this study are scientific journals and articles that support and are relevant to the title of this article. According to the commentators Nasiyah is the central crown where the orders of all the organs of the human body. In Nasiyah (the crown) it is based on character, because the owner of the crown is the cause of an action. Nasiyah itself does not just mean the crown but also includes the entire human body. Then the relationship between character formation and the human brain is a character located in the frontal lobe and parietal lobe. Based on the views of commentators and scientific scientists on the meaning of nashiyah in the Qur’an, that when the crown is damaged, this will have an impact on changes in human behavior and mindset. When in the afterlife humans are physically tortured, the first and foremost organ of the body that will feel the torment is the crown. Because, the crown is what will give the color of good and bad to human actions.